Priority setting of ICU resources in an influenza pandemic: a qualitative study of the Canadian public's perspectives - Silva Diego S; Gibson Jennifer L; Robertson Ann; Bensimon Cécile M; Sahni Sachin; Maunula Laena; Smith Maxwell J (BMC, 2012)
Abstract Background Pandemic influenza may exacerbate existing scarcity of life-saving medical resources. As a result, decision-makers may be faced with making tough choices about who will receive care and who will have to wait or go without. Although previous studies have explored ethical issues in priority setting from the perspective of clinicians and policymakers, there has been little investigation into how the public views priority setting during a pandemic influenza, in particular related to intensive care resources. Methods To bridge this gap, we conducted three public town hall meetings across Canada to explore Canadian's perspectives on this ethical challenge. Town hall discussions group discussions were digitally recorded, transcribed, and analyzed using thematic analysis. Results Six interrelated themes emerged from the town hall discussions related to: ethical and empirical starting points for deliberation; criteria for setting priorities; pre-crisis planning; in-crisis decision-making; the need for public deliberation and input; and participants' deliberative struggle with the ethical issues. Conclusions Our findings underscore the importance of public consultation in pandemic planning for sustaining public trust in a public health emergency. Participants appreciated the empirical and ethical uncertainty of decision-making in an influenza pandemic and demonstrated nuanced ethical reasoning about priority setting of intensive care resources in an influenza pandemic. Policymakers may benefit from a better understanding the public's empirical and ethical 'starting points' in developing effective pandemic plans.